Letramento funcional em saúde e qualidade de vida de adolescentes do ensino médio de escolas estaduais de Belo Horizonte - Poliana Cristina Rocha (2015)
Introduction: the functional literacy on health is made by the individual's ability to handle and manage health information necessary for his/her self-care or relationships with healthcare professionals. So, studying the functional literacy in health in adolescents can help develop health promotion strategies for this cycle of life. Objective: to investigate the association between functional health literacy and quality of life of adolescents. Methods: to accomplish the objective, the study was conducted in two steps, the first being constituted by a literature review and the second, a field search. The integrative review of literature was produced according to the functional literacy themes in health and quality of life, with search performed in the databases PubMed, Lilacs, Biblioteca Virtual em Saúde. After applying the inclusion criteria, yielded 538 articles, and after the application of the exclusion criteria 11 articles were selected, nine being international and two national studies. The review consisted of compilation and historical line construction of publications and methodological analysis of observational studies. The field search was a cross-sectional analytical observational design with simple random probability sample of adolescents aged between 15 and 19 years old, attending high school in one of the 131 state schools in Belo Horizonte, Minas Gerais, distributed by the regional administrates (Centro-Sul, Oeste, Pampulha, Nordeste, Leste, Noroeste, Venda Nova, Barreiro e Norte). For data collection were used questionnaires of adolescents characterization, quality of life (PedsQL version 4.0), functional literacy in health and self-perception of health and violence. For the analysis of data, descriptive analysis of the frequency distribution of categorical variables and analysis of central tendency and dispersion for continuous variables were performed. Then multivariate logistic regression analysis with hierarchical data entry according to the level of determination of the established theoretical model was performed. The variables with statistically significant associations at the level of 20% (p <0.20) in the bivariate analysis were considered in models of multiple logistic regression. To evaluate the associations in logistic regression models, the significance level of 5% was considered. As a measure of the magnitude of the associations we used the Odds Ratio and its respective 95% confidence interval. The adequacy of the models was assessed using the Hosmer and Lemeshow test. Results: the literature review indicated a statistically significant association between functional literacy in health and socio-demographic variables (gender, age and education). Most of the studies aimed to relate literacy to pathologies and was conducted in clinical settings (clinics and hospitals). Of the eight observational articles included in this review only one fully met the methodological criteria in developing this type of study. Field survey results revealed that 51.56% of adolescents had good functional literacy in health. In the final model of multivariate analysis, the variables: not practicing religion (p = 0.006; OR = 2.108); social domain of quality of life (p = 0.004; OR = 1,022); and school field of quality of life (p = 0.009; OR = 1.019) remained associated with functional literacy in health. Conclusion: The study indicated that most of the research conducted in the area show association between functional literacy in health and sociodemographic characteristics. In the field search, most of the sample showed good functional health literacy. The variables associated with statistical significance to functional literacy on health were not been practicing any religion and social and educational domains of quality of life.